Use of the Brief Observation of Symptoms of Autism (BOSA) as a new clinical approach to assessing patients with suspected spectrum disorder during the COVID-19 pandemic - Rynkiewicz, Agnieszka; Vasa, Roma; Łucka, Izabela; Mazur, Artur (Pediatria Polska - Polish Journal of Paediatrics, 2020)
COVID-19 has imposed major changes to the delivery of healthcare worldwide. In many settings, healthcare is now predominantly transitioned to telehealth, creating challenges and unique benefits. In 2020, the Centers for Disease Control and Prevention has reported that 1 in 54 children in the U.S. are diagnosed with autism spectrum disorder (ASD). The Brief Observation of Symptoms of Autism (BOSA) is a new clinical approach that has been developed to ensure that patients suspected of ASD can receive valid diagnostic assessments during the pandemic. BOSA is offered when a diagnostician is unable to administer the Autism Diagnostic Observation Schedule – Second Edition (ADOS-2) either because it is not appropriate to administer the ADOS-2 via telehealth or, in person, face coverings confound ASD assessment. Only trained ADOS-2 diagnosticians can administer BOSA, because BOSA relies on ADOS-2 codes. The article describes BOSA to prepare the field for future research during the COVID-19 crisis.